2022
DOI: 10.24191/ji.v17i2.18213
|View full text |Cite
|
Sign up to set email alerts
|

Rail Service Quality and Customer Satisfaction in Malaysia

Abstract: The purpose of the research is to analyze the relationship between rail service quality and customer satisfaction. A total of 356 sets of questionnaires were distributed via email to passengers of rail transport in Malaysia and a total of 258 questionnaires were usable for the analysis. Using Pearson correlation analysis and multiple regression analysis our research found that only four rail service quality dimensions namely reliability, responsiveness, convenience, and connection are significant in predicting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…This study also discusses the critical elements of responsiveness in public transport services, emphasizing both the willingness and promptness to serve customers as one of the important elements influencing the traveller's satisfaction (Ong, 2022). Timeliness is crucial, as customers are unwilling to endure inefficiency and may resort to private cars, particularly observed in the commuter service in Klang Valley (Ali et al, 2022). Employee responsiveness, demonstrated through quick responses to inquiries and requests, plays a pivotal role in customer satisfaction.…”
Section: Responsivenessmentioning
confidence: 99%
“…This study also discusses the critical elements of responsiveness in public transport services, emphasizing both the willingness and promptness to serve customers as one of the important elements influencing the traveller's satisfaction (Ong, 2022). Timeliness is crucial, as customers are unwilling to endure inefficiency and may resort to private cars, particularly observed in the commuter service in Klang Valley (Ali et al, 2022). Employee responsiveness, demonstrated through quick responses to inquiries and requests, plays a pivotal role in customer satisfaction.…”
Section: Responsivenessmentioning
confidence: 99%
“…In railway studies, measuring service quality for public transport has two dimensions: the first would be the objective dimension, whereby, service quality is objectified in performance indicators such as frequency and speed while the subjective dimension measures service quality through consumer judgments (Eltayeb, 2017). A study in Indonesia states that RAILQUAL was used on intercity trains in the country, such as platform and in-train services, found punctuality (reliability), employee services, and security (assurance) significantly influenced satisfaction among their respondents (Ali et al, 2022). Based on studies, punctuality, reliability, network connection, and service frequency were highly appreciated characteristics of public transport in Munich.…”
Section: Accessibilitymentioning
confidence: 99%
“…In the context of rail transportation, customer satisfaction can be defined as the feeling of passengers towards how their actual experience meet their expected service quality (Ali et al, 2021;Wonglakorn et al, 2021;Wang et al, 2020). It has also been found that customer satisfaction is an effective performance indicator of service quality (Trompet et al, 2013;Ngoc et al, 2017;Liangrokapart, 2021).…”
Section: Customer Satisfaction and Frequency Of Usementioning
confidence: 99%